THE SUCCESS FACTORS OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC (SURVEY ON VOCATIONAL SCHOOL STUDENTS IN MEDAN CITY) (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
This study aims to describe the success factors of online learning during the Covid-19 pandemic for vocational school students in Medan City. The four success factors of online learning used are teacher characteristics, student characteristics, technology, and support. This research is an explanatory survey research with data collection techniques through a questionnaire summarized in 53 questions distributed to 101 students at SMK Laksamana Martadinata Medan City. The data collected was then analyzed using the Guttman Scale. The results of this study indicate that online learning for students of SMK Laksamana Martadinata Medan has been successfully implemented.